An examination of cost structure and production performance of commercial banks in Singapore - Rezvanian, Rasoul; Mehdian, Seyed (Journal of Banking & Finance, 2002)
This paper uses a parametric approach in the framework of a translog cost function and a non-parametric approach in the framework of linear programming to examine production performance and cost structure of a sample of Singaporean commercial banks. The results of the parametric methodology suggest that the average cost curve of these banks is U shaped and there are economies of scale for small and medium-size banks. Further analysis provides evidence of economies of scope for all banks regardless of their size. The non-parametric results indicate that the Singaporean banks could have reduced cost by 43% had they all been overall efficient. The sources of this cost inefficiency seem to be caused equally by allocative and technical inefficiencies.